HEALTH INSURANCE COVERAGE, AGE, AND IMMIGRATION-RELATED FACTORS AMONG KOREAN AMERICANS. (20th December 2022) - Hong, Seunghye; Park, Ki Tae; Lee, Yeonjung; Park, Mei Linn; Park, Nan Sook
Abstract: The purpose of this study was to examine health insurance coverage and its association with demographic and immigration-related factors (English proficiency, generational status, and age at immigration) among Korean Americans (KAs, n=11, 462). Data were drawn from the 2017 American Community Survey. KA older adults aged 65+ had significantly higher odds of having any health insurance compared to those aged 41 to 64. KAs who speak English well or only speak English were more likely to have any health insurance compared to those with limited English proficiency (i.e., don't speak English well or at all). First-generation KAs had lower odds of having any health insurance compared to those born in the U.S. Those who immigrated after 41 years of age were less likely to have health insurance compared to those born in the U.S. These findings underscore the need to consider immigration-related factors in efforts to increase healthcare accessibility for KAs.